The Economic Consequences of the Covid-19 First Wave and the New International Scenarios. An Historical Dimension - Amedeo Lepore; Stefano Palermo; Andrea Pomella (European Scientific Journal, ESJ, 2022)
The Covid-19 crisis is urging scholars to ponder the perspectives of the globalization process which started at the end of the XXth Century. The pandemic is creating a sense of insecurity and uncertainty which has few precedents in the current age, pervading wider and wider sectors of the population. Moving from the analysis of the first wave of the pandemic (March 2020), this essay proposes a model of analysis of the effects of the pandemic by framing the economic emergency produced by it from a historical and theoretical perspective. The paper will also try to indicate the traits and the model of a new economic paradigm: the birth of a new globalization that would surely feature competitions between its biggest geoeconomics areas, but that would also offer the opportunity to promote novel perspectives for development and to achieve a brand-new convergence between the private and public interest.